2016
DOI: 10.14569/ijacsa.2016.070217
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Responsibility in Combating Online Misinformation

Abstract: Abstract-In the age of mass information and misinformation, the corporate duty of developers of browsers, social media, and search engines are falling short of the minimum standards of responsibility. The tools and technologies are already available to combat misinformation online but the desire to integrate these tools has not taken enough priority to warrant action. This paper presents an effective and practical method based on technologies already available that could be used for browsers and social media w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…With regards to the fourth strategy, the use of ranking, selection and removal mechanisms by online platforms, one paper goes so far as to say that it is the “corporate duty of developers of browsers, social media, and search engines” to combat online misinformation (Safieddine, Masri, & Pourghomi, 2016). This is related to the ongoing debate played out in academia, media, and even government of whether platforms are publishers with associated responsibility for content or not (Gillespie, 2010; House of Lords, 2018; LSE, 2018; TheGuardian.com, 2018).…”
Section: What Can Be Done About Misinformation About Climate Change?mentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the fourth strategy, the use of ranking, selection and removal mechanisms by online platforms, one paper goes so far as to say that it is the “corporate duty of developers of browsers, social media, and search engines” to combat online misinformation (Safieddine, Masri, & Pourghomi, 2016). This is related to the ongoing debate played out in academia, media, and even government of whether platforms are publishers with associated responsibility for content or not (Gillespie, 2010; House of Lords, 2018; LSE, 2018; TheGuardian.com, 2018).…”
Section: What Can Be Done About Misinformation About Climate Change?mentioning
confidence: 99%
“…A summary of the potential ways to counteract misinformation found in the literature, along with their criticisms and caveats [1: Cook et al, 2018; 2: Zucker, 2019; 3: Roozenbeek & van der Linden, 2019; 4: Epstein et al, 2019; 5: Lutzke et al, 2019; 6: Sullivan et al, 2014; 7: Hess & Collins, 2018; 8: Bedford, 2010; 9: Bedford et al, 2014; 10: Bedford & Cook, 2013; 11: Legates et al, 2013; 12: Legates et al, 2015; 13: McNeal et al, 2014; 14: Cook et al, 2017; 15: Cook et al, 2015; 16: van der Linden et al, 2017; 17: Shao, Ciampaglia, et al, 2018; 18: Safieddine et al, 2016; 19: Pennycook & Rand, 2019; 20: Fernandez & Alani, 2018; 21: Vicario et al, 2016; 22: Leetaru, 2018; 23: Pew Research Center, 2017; 24: Mavrovic, 2018; 25: Henley, 2018; 26: European Commission, 2018; 27: Lawrence & Estow, 2017; 28: Kahan, 2017; 29: Benegal & Scruggs, 2018; 30: Harvey et al, 2018; 31: Nyhan & Reifler, 2010; 32: Garrett & Weeks, 2013; 33: Anderson et al, 1980; 34: Thorson, 2016; 35: Funke, 2019; 36: ALA, 2019; 37: Tompros et al, 2017]…”
Section: What Can Be Done About Misinformation About Climate Change?mentioning
confidence: 99%
“…Considering the dark side of social networks, the environment facilitates the arrangement of groups and campaigns with the intention of undertaking unethical activities as well as mimicking widespread information diffusion behavior [4], [10]. Consequently, this facilitation of potential misconducts in online environments has encouraged some users to spread misinformation that results in greater support to cult-like views in a variety of topics [5]. What is more, those views are sometimes contagious and the individuals behind them make great efforts to spread them to others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a prior publication [5], the authors suggested an approach to combating misinformation on social media. The team proposed an automated approach, dubbed as 'Right-click Authenticate' option that could review, rank, and identify misinformation using tools already found online.…”
Section: The 'Right-click Authenticate' In Combating Misinformation Omentioning
confidence: 99%
See 1 more Smart Citation